The Effect of Use Styrofoam for Flexural Characteristics of Reinforced Concrete Beams - . Yasser; Herman Parung; M. Wihardi Tjaronge; Rudy Djamaluddin (International Conference on Engineering and Technology Development (ICETD), 2013)
In general bending loads acting on structural elements of concrete beams arrested by the bottom cross secttion on the compression area while the tension area is ignored. Therefore, it is reasonable if the concrete beam section on the tension area is minimized with concrete mass reduction in tensile region by ignoring concrete tensile stress while receiving static loads or the area is filled with styrofoam concrete (styrocon). One effort to effeciency concrete economic value by reducing the concrete and use of styrocon thus component volume of natural materials, such as sand mining, coarse aggregate, and cement and weight of construction becomes smaller. Styrofoam as waste can be used as filler to reduce the volume of concrete, especially for areas where the concrete section is not working mechanically. In an effort to study the flexural strength of external reinforced concrete beams and styrofoam-filled composite, then performed a series of tests. Test material in the form of beams with dimensions of 15 cm x 20 cm x 270 cm. Test material consisted of normal beam quality 26.0 MPa concrete with transverse reinforcement as a control beam and test materials with external transverse reinforced and truss systems and styrofoam-filled composite. In the normal-styrocon composite beams with various content of styrofoam. Beam placed on 2 simple supports with 2 point loading test method. Results showed flexural capacity of the normal concrete beam is 36.7 kN, but the external reinforced beams decreased 30.6 kN, but external reinforced truss system beams is relatively equal 35.8 kN. But external reinforced beams prone to corrosion and fire and require maintenance. Therefore used styrocon on the outer portion with styrofoam content of 30%, 40%, and 50% who had a flexural strength of each 33.8 kN, 31.0 kN and 29.0 kN. It can be concluded that the use of composite concrete beams normal-styrocon can efficiency use natural materials to reduce the weight of the concrete beam and construction as well as having environmental aspects by using the waste.